The impact of school closures during the COVID-19 pandemic on reading fluency among second grade students: socioeconomic and gender perspectives - Shaul, Shelley; Lipka, Orly; Tal-Cohen, Dana; Bufman, Adi; Dotan, Shahar (Frontiers in Psychology, 2024)
The acquisition of reading skills is a crucial milestone in early education, with formal instruction and practice playing pivotal roles. The outbreak of COVID-19 led to widespread school closures and a shift to remote learning. This study aimed to investigate the effects of school closures on reading acquisition and fluency among a large sample of second-grade children, considering socioeconomic status (SES) and gender differences. In 2019, a cohort of 2228 second-grade students from 34 schools was assessed for word reading fluency and comprehension. In 2020, during the pandemic, 765 students from a subsample of 20 original schools were re-evaluated using the same measures. The study also collected school-related data.The findings from the entire sample indicated no significant differences in fluency and comprehension scores between children in the second grade in 2019 and 2020. However, a significant interaction emerged when analyzing low SES versus high SES children. Children from low SES backgrounds exhibited notably lower reading scores after a year of remote learning due to the COVID-19 outbreak. Moreover, the disparity in reading scores between low SES and high SES children nearly doubled in 2020. Gender differences were also detected.These results underscore the impact of remote learning during the COVID-19 crisis on exacerbating gaps in reading fluency and comprehension between children from high and low SES backgrounds. The implications of these findings highlight the critical role of in-person schooling and targeted support for disadvantaged students, especially during pivotal stages of reading development.